PENERAPAN PENDIDIKAN KESEHATAN TERHADAP KEPATUHAN PERAWAT CUCI TANGAN LIMA MOMEN DI RUANG TERATAI 1 RS. BHAYANGKARA TK. I R. SAID SUKANTO JAKARTA - Jesy Milanti (2022)
Nurses are health workers who are most likely to occur nosocomial infections. Hand hygiene compliance is a basic thing that can be done for infection prevention and control. Nurses in the Teratai 1 room have not 100% implemented the five moments of hand hygiene. Writing this scientific paper aims to analyze the increase in nurse compliance in the Teratai 1 room in applying five times of hand hygiene for nurses who are given health education interventions and those who are not given interventions. The number of nurses who received health education intervention was 10 people and three people did not receive intervention. The results of the evaluation showed that there was an effect of health education on compliance with applying the five moments on hand to nurses who had health education interventions P-value = 0,000 < α 0,05 and nurses who did not receive health education interventions P-value = 0,038 < α 0,05. The PPI team must always supervise, control, and motivate the implementation of the five times of hand washing and provide sanctions for nurses who do not comply and provide rewards for those who are always obedient in applying the five times of washing hands. Hospitals are expected to be able to provide more frequent training and seminars related to hand hygiene.